The Effect of Debriefing and Brief Cognitive-Behavioral Therapy on Postpartum Depression in Traumatic Childbirth: A Randomized Clinical Trial - Sedigheh Abdollahpour; Afsaneh Keramat; Seyyed Abbas Mousavi; Ahmad Khosravi; zahra motaghi (Mashhad University of Medical Sciences, 2018)
Background & aim: Childbirth is a stressful event in women's lives, and if a mother perceives it as an unpleasant event, it can influence her postpartum mental health. Depression is a common mental disorder, which can has serious consequences depending on its severity. Therefore, this study aimed to investigate the effect of debriefing and brief cognitive-behavioral therapy on postpartum depression in traumatic childbirth. Methods: This clinical trial was performed on 179 mothers who experienced a traumatic childbirth and were admitted in postnatal ward of Nohom Dey Hospital in Torbat-e Heydarieh, North East of Iran in 2016. The subjects were randomly allocated into three groups, including two intervention groups of debriefing and brief cognitive-behavioral counseling and a control group. The intervention groups received appropriate counseling for 40-60 minutes in the first 48 postpartum hours and the control group received the routine postpartum care. Edinburgh Postnatal Depression Scale was used to evaluate postpartum depression 4-6 weeks and also three months after the intervention. Post-traumatic stress symptoms in were compared in three groups using t-test, chi-square test, and repeated measures analysis of variance. Results: No significant differences were observed between the mean depression scores of the two intervention groups and that of the control group 4-6 weeks after childbirth. However, three months after delivery, the mean depression scores of the two intervention groups was lower than the control group (P